SOCIO-ECONOMIC AND ENVIRONMENTAL IMPACTS OF MATCH 2011 EARTHQUAKE, TSUNAMI AND FUKUSHIMA NUCLEAR ACCIDENT IN JAPAN - BACHEV, Hrabrin (Journal of Environmental Management and Tourism, 2016)
On March 11, 2011 the strongest recorded in Japan earthquake occurred which triggered a powerful tsunami and caused a nuclear accident in the Fukushima Daichi Nuclear Plant Station. The triple 2011 disaster has had immense impacts on people life, health and property, social infrastructure and economy, agri-food chains, natural and institutional environment, etc. in North-eastern Japan and beyond Due to the scale of the disasters and the number of affected agents, the effects’ multiplicities, spillovers, and long time horizon, the constant evolution of the nuclear crisis, the lack of “full” information and models of analysis, etc. the overall impacts of the 2011 disasters is far from being completely evaluated. Besides most information and publications are in Japanese. The goal of this paper is to assess the socio-economic and environmental impact of Match 2011 earthquake, tsunami and Fukushima nuclear accident in Japan. Firstly, a short description of the three events is presented. Next, the overall impacts on population, health and displacement assessed. Third, the effects of economy are evaluated. After that, diverse impacts on agri-food chains are presented. Finally, the impact on natural environment is assessed. A wide range of official governmental, farmers, industry and international organisations, and Tokyo Electric Power Company data as well as information from publications in media, research and experts reports, etc. have been extensively used.
Keywords: social; economic; agri-food chain; environmental impact; Great East Japan Earthquake; March 11; 2011 earthquake and tsunami; Fukushima nuclear accident; disaster risk managment; Japan